Dual‐Comb Lasers: Dual‐Comb Femtosecond Solid‐State Laser with Inherent Polarization‐Multiplexing (Laser Photonics Rev. 15(8)/2021). Issue 8 (13th August 2021) - Kowalczyk, Maciej; Sterczewski, Łukasz; Zhang, Xuzhao; Petrov, Valentin; Wang, Zhengping; Sotor, Jarosław
Abstract : In article number 2000441, Maciej Kowalczyk and co‐workers developed a novel technique for simultaneous generation of two pulse trains from a single femtosecond laser. It is based on polarization‐multiplexing in a birefringent gain medium and allowed to achieve the lowest relative noise ever demonstrated for any solid‐state dual‐comb laser. This simple technique can be utilized for free‐running, but yet very precise spectroscopic measurements.